CLASSICAL SIGNIFICANCE AND VARIOUS ASPECTS OF BHOJANA (MEAL) AND BHĀJANA (UTENSIL) AS PER ĀYURVEDA- A CLASSICAL ANALYSIS (AYUSHDHARA, 2021)
Food is considered to be the path of health and salvation. Desire of food, easy digestion of ingested food, proper excretion of feces, urine and flatus, lightness of body, longevity and happiness are known to be features of health. Health is dependent upon food and the food looks for proper method. In the present era, everyone wants to know only about tasty food, but people are not much aware of the rules of food preparation, rules of proper intake, and proper utensils for food intake, etc. Practicing appropriate diet-regimen, pertinent demeanor, appropriate sleep and wake up makes a person devoid of distress. In this way a vast description of salutary diet regimen is available in the treatise of Āyurveda. This paper deals with the use of utensils and methodology of food intake mentioned in Kaśyapa Saṃhitā and other Ayurvedic scriptures.